Synthesis of new N-aryl-2-[(4-amino-4H-1,2,4-triazolo-[4,3-b]pyridazin-3-yl)thio]acetamide derivatives - Severina, A.I.; Yanchenko, V.A.; Hayrulin, A.R.; Georgiyants, V.A.; Demchenko, A.M. (Журнал органічної та фармацевтичної хімії, 2009)
N-aryl-2-[(4-amino-4H-1,2,4-triazol-3-yl)thio]acetamides were prepared by interaction of 4-amino-1,2,4-triazolyl-3-thiol with N-aryl-2-chloroacetamides. The condensation of N-aryl-2-[(4 -amino-4H~1,2,4-triazol-3-yl)thio]acetamides with pentane-2,4-dione resulted in the formation of N-aryl-2-[(6,8-dimethyl[1,2,4]triazolo[4,3-b]pyridazin-3-yl)thioJacetamide derivatives. N-арил-2-[(4-аміно-4Н-1,2,4-триазол-3-іл)тіо]ацєтаміди були отримані взаємодією 4-амі-но-1,2,4-триазоліл-З-тіолу із N-арил-2-хлороацетамідами. Конденсацією N-арил-2-[(4-аміно-4Н-1,2,4-триазол-3-іл)тіо]ацетамідів із пентан-2,4-діоном отримані похідні N-арил-2-[( 6,8-димєтил[ 1,2,4]триазоло[ 4,3-b]піридазин-3-іл)тіо ]ацетаміду. N-арил-2-[(4-амино-4Н-1,2,4-триазол-3-ил)тио]ацетамиды были получены взаимодействием 4-амино-1,2,4-триазолил-З-тиола с N-арил-2-хлороацетамидами. Конденсацией N-арил-2-[(4-амино-4Н-1,2,4-триазол-3-ил)тио]ацетамидов с пентан-2,4-дионом получены производные N-арил-2-[(6,8-диметил[1,2,4]триазоло[4,3-b]пиридазин-3-ил)тио]ацетамида.